2009
DOI: 10.2340/00015555-0724
|View full text |Cite
|
Sign up to set email alerts
|

HLA Typing in an IFN- -induced Scar Sarcoidosis: Possible Pathogenetic and Clinical Implications

Abstract: SinSarcoidosis as a complication ofinterferon (IFN) administration was first described in 1987 in a patient with renal cancer (I). Since then, more than 50 cases of pulmonary and/or cxtra-puhnonary sarcoidosis. mainly occurring in middle-aged women, have been correlated with IFN-a therapy, sometimes associated with ribavirin, in patients with chronic viral hepatitis C (2.3). Several lines of evidence suggest that HLA class I and class II alíeles may be considered possible markers for susceptibility, clinical b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
2
7
0
1
Order By: Relevance
“…Eski yaraların in ltrasyonu ya da bu bölgelerde yeni gelişen küçük kırmızı-kahverengi nodüller şeklinde karşımıza çıkabilmektedir. Eski skar alanlarının neden etkilendiği henüz tam olarak aydınlatılamamakla birlikte genetik olarak yatkınlığı olan bireylerde sarkoidozda aktive olmuş T hücre aracılı immün yanıtın travma ile ilişkili olarak dokuyu persiste eden yabancı cisme karşı yönelmesi sonucu skar sarkoidozunun gelişebildiği ya da paterji reaksiyonunun özel bir formu olabileceği bildirilmiştir 8,9 . Skar sarkoidozu ile sistemik hastalık aktivitesi arasında paralellik olduğu düşünülmektedir.…”
Section: Discussionunclassified
“…Eski yaraların in ltrasyonu ya da bu bölgelerde yeni gelişen küçük kırmızı-kahverengi nodüller şeklinde karşımıza çıkabilmektedir. Eski skar alanlarının neden etkilendiği henüz tam olarak aydınlatılamamakla birlikte genetik olarak yatkınlığı olan bireylerde sarkoidozda aktive olmuş T hücre aracılı immün yanıtın travma ile ilişkili olarak dokuyu persiste eden yabancı cisme karşı yönelmesi sonucu skar sarkoidozunun gelişebildiği ya da paterji reaksiyonunun özel bir formu olabileceği bildirilmiştir 8,9 . Skar sarkoidozu ile sistemik hastalık aktivitesi arasında paralellik olduğu düşünülmektedir.…”
Section: Discussionunclassified
“…African Americans have about a threefold higher annual incidence as compared with that of Caucasion Americans 15 . Racial differences are probably influenced by environmental exposure, predisposing HLA alleles and other genetic factors 1,6,11,16 . HLA classes I and II are associated with sarcoidosis and IFN-induced sarcoidosis patients were positive for the predisposing HLA profile 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the association between sarcoidosis and chronic hepatitis C. According to the literature, sarcoidosis rarely occurs in hepatitis C virus (HCV) patients and it is associated with interferon (IFN) treatment 1,3 . Only a few cases of IFN induced sarcoidosis have been reported in the English literature [3][4][5][6][7][8][9][10][11] . IFN has an antiviral property and it has become the standard treatment for chronic HCV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Then, we identified 2 major haplotype of the IFN-α gene and found that an IFNA allele, overrepresented in patients with sarcoidosis, was subsequently associated with increased IFN-α and IL-12 production in vitro [8]. Moreover, in a recent reported case of IIS, HLA typing was performed and revealed that the patient was positive for HLA-DRB1*03 and HLA-DQB1*02 [62], which have a correlation with the disease course or prognosis in sarcoidosis [63][64][65]. The authors hypothesized that this HLA profile predisposed the patient to IIS development [62].…”
Section: Most Patients With Iis Had Resolution Of Their Disease Withomentioning
confidence: 99%